IMF Staff papers : Volume 22 No. 1. (IMF Staff Papers; IMF Staff Papers, 1975)
This paper provides a survey of some major issues of incomes policy rather than an evaluation of individual countries' policies. It seeks to highlight and explain the changing emphasis of such policies in the three periods when they were widely adopted. After the War, incomes policies were implemented in several European countries, in the context of scarcities of goods and shortage of foreign exchange. Policies involving a considerable element of compulsion were then associated with other restrictions, such as direction of labor and rationing. At current high rates of inflation and of unemployment, there is growing recognition of the threat that inflation poses to political and economic institutions. Although the recent results of incomes policy have not been striking, present circumstances may be more conducive for success. Experience suggests that incomes policy may be most effective in restraining wage and price increases under conditions of less than full employment.